1969
DOI: 10.1103/physrev.183.1200
|View full text |Cite
|
Sign up to set email alerts
|

51 000τDecays

Abstract: An analysis has been made of 51 000 K~ -> 7r~x~7r + decays in flight in the Berkeley 25-in. hydrogen bubble chamber. After corrections for detection efficiency and Coulomb interactions, the projections of the pion spectra have been fitted with expansions in the Dalitz variables X and F. In addition, maximumlikelihood fits to the entire Dalitz plot have been made. The decay distribution is well described by 1+aF, where the slope Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

1969
1969
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…For (A), the agreement with data is still good, which is the well known result of the chiral unitary model [1,3,8]. Originally the subtraction constants in the S = −1 channel are not very [16,17,18,19,20,21,22,23,24]. much dependent on the channels and take values around a i ∼ −2 as shown in Table I.…”
supporting
confidence: 67%
“…For (A), the agreement with data is still good, which is the well known result of the chiral unitary model [1,3,8]. Originally the subtraction constants in the S = −1 channel are not very [16,17,18,19,20,21,22,23,24]. much dependent on the channels and take values around a i ∼ −2 as shown in Table I.…”
supporting
confidence: 67%
“…Hence the first ratio indicated a violation of the A/ = ^ rule ini£ + -*37r decay. Similar results are obtained in the experiment of Mast et al 13 on T~ decays where a T -is found and compared with existing r /+ data. There are also indications of violation of the A/= \ rule in K -3TT branching ratio experiments.…”
supporting
confidence: 90%
“…If there are more than one elements in G which vanish, we can follow the procedure recursively and finally solve a symmetric system instead of a general system. In this thesis work we studied different kinds of data including the K-p scattering sections [37,38,39,40,41,42,43,44,45,46], the K-p threshold branching ratios, the 7rZ mass spectrum for K-p .4 7r+_r-(_-Tr+), and the 7r°A mass spectrum for K-p --_ 7r+Tr-(Tr°A). In the rest of this chapter, we will first shown how to compute these experimental observables from the CBM theory.…”
Section: Solving For T-matrix Elementsmentioning
confidence: 99%
“…Also, at K-momenta around 390 MeV/c, there is a clear signal of A(1520) which is a D-wave resonance [37]. The data (either read from tables or off graphs) are from references [37,38,39,40,41,42,43,44,45,46] and are plotted in Fig. 5, .…”
Section: R-_+ 7r°amentioning
confidence: 99%